Current State of Evidence on Kidney Transplantation: How Fragile Are the Results?. Issue 2 (6th May 2021) - Budhiraja, Pooja; Kaplan, Bruce; Kalot, Mohamad; Alayli, Abdallah El; Dimassi, Ahmad; Chakkera, Harini A.; Heilman, Raymond; Edwards, Audrene S.; Mustafa, Reem A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The study aims is to use the fragility index (FI) to examine the strength of evidence of randomized controlled trials (RCTs) published in the last decade on kidney transplantation. Methods: We searched MEDLINE for studies on kidney transplantation. We included the RCTs that compared 2 groups with 1:1 randomization and reported significant P values (<0.05) for a dichotomous outcome and were published in the top 10 transplant journals. We calculated the FI; a calculation used to determine the minimum number of subjects needed to change from a nonevent to an event to make the study results nonsignificant ( P  ≥ 0.05). Results: Fifty-seven RCTs met our inclusion criteria. The median sample size was 100 participants in each arm, the median number of events was 16 (interquartile range, 8–30) in the intervention group. Among the included trials, 79% were industry-funded, 93% involved medications, and the majority were open label. The median FI was 3 (interquartile range, 1–11). In 43% of the trials, the number of patients reported lost to follow-up was higher than or equal to the FI. Only 4% of the RCTs imputed a value for the missing dichotomous outcome. Furthermore, the median number of subjects who discontinued the trial because of adverse effects was 21, which was greater than the FI in 60% of the RCTs. Conclusions: The arbitrary classification of results into "significant" and "nonsignificant" based on P  value <0.05 should perhaps be interpreted with the help of other statistical parameters and FI is one of them.